PTU-093 Hcc Diagnosed on Surveillance Programmes: impact on Stage and outcome. (4th June 2013) - Ahmed, A; Mustafa, Z; Neilson, M; Rutherford, M; Ballantyne, S; Kasthuri, R; Evans, J; Forrest, E H; Barclay, S; Gillespie, R; Priest, M; Mills, P R; et al.
Abstract : Introduction: Surveillance of cirrhotic patients for HCC is recommended by numerous national and international guidelines. However many patients are still diagnosed de novo with this malignancy. Data on the benefits of surveillance remains relatively limited. Our aim was to compare stage at diagnosis and patient outcome for those diagnosed on surveillance and those who were not. Methods: Using our regional HCC MDT database, we analysed patients diagnosed with HCC between January 2009 and January 2012. All patients were staged using the Barcelona Clinic Liver Cancer (BCLC) system. We compared the stage at diagnosis, the treatment strategy after MDT discussion, and the survival in those diagnosed in surveillance with those diagnosed de novo. Statistical comparisons were made using CHI-squared or Kaplan Meier analysis as appropriate. Results: 190 patients were diagnosed with HCC at MDT during the study period. We had full follow-up data on 169 patients which were used for analyses, with mean follow up 10 months. Mean age was 68 years and 82% patients were male. Aetiology was alcoholic liver disease in 32% and HCV in 15%. 38 (22%) patients were in surveillance programmes at diagnosis of HCC and 132 (78%) were not. Tumours were BCLC stage A at diagnosis in 28.9% patients in surveillance, compared with 6.1% not in surveillance (p = 0.0003). 15.8% those diagnosed in surveillance underwent transplantation or resection, compared with 2.3% who were not (p = 0.004). Survival for those diagnosed in surveillance was greater than those diagnosed de novo (p = 0.01) Conclusion: Most patients diagnosed with HCC in our region were not in surveillance programmes. Patients diagnosed on surveillance were more likely to have potentially curative disease and had higher overall survival. Disclosure of Interest: None Declared References: EASL Clinical practise guidelines: Management of hepatocellular carcinoma. J Hepatol 2012; 56:908–943 AASLD Practice Guidelines management of Hepatocellular Carcinoma: An update. Hepatol 2010; 53(3):1021–1022 APASL consensus on HCC. Hepatol Intern 2010; 4:439–74